(untitled) (Medical Forum Monthly, 2025)
Objective: To investigate the correlation between intercondylar distance (ICD) and occlusal vertical dimension (OVD) in a segment of the Pakistani Asian population, and assess whether ICD can serve as a reliable anatomical landmark for determining OVD in dentate individuals.Study Design: Cross-sectional analytical studyPlace and Duration of Study: This study was conducted at the Islamic International Dental Hospital, Islamabad, from January 2024 to December 2024.Methods: A total of 160 dentate individuals (80 males, 80 females) aged 18–30 years with Class I occlusion were selected through randomized sampling. ICD was measured using the Denar reference point and a modified digital vernier caliper. OVD was assessed using a Willis Gauge. The Shapiro-Wilk test was applied to evaluate data normality. Gender-based differences were assessed using the Mann-Whitney U test, while the relationship between ICD and OVD was evaluated using Spearman’s correlation.Results: The mean ICD was 132.1 mm in males and 123.7 mm in females, revealing a statistically significant difference (p = 0.001). The mean OVD was 49.3 mm in males and 50.4 mm in females, with no significant gender difference (p = 0.29). Spearman’s correlation showed a weak, non-significant association between ICD and OVD (ρ = 0.18, p = 0.25).Conclusion: ICD significantly differs by gender, while OVD does not. No statistically significant correlation was found between ICD and OVD, indicating ICD alone may not be a reliable predictor for determining OVD.